2022
DOI: 10.1101/2022.09.08.507172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crosstalk between RNA m6A and DNA methylation regulates transposable element chromatin activation and cell fate in human pluripotent stem cells

Abstract: Transposable elements (TEs) are parasitic DNA sequences accounting for over half of the human genome. Tight control of the repression and activation states of TEs is critical for genome integrity, development, immunity, and diseases, including cancer. However, precisely how this regulation is achieved remains unclear. To address this question, we develop a targeted proteomic proximity labeling approach to capture TE-associated proteins in human embryonic stem cells (hESCs). We find that the RNA N6-methyladenos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Comparing the E006AA-hT and LNCaP prostate cancer cell lines, which have low versus high LINE-1 expression, respectively, they identified known LINE-1 associated TFs such as CTCF and YY1, as well as a novel LINE-1 repressor, dual phosphatase 1 (DUSP1). Sun et al used another variant of proximity labeling called "TurboID" [195] to identify factors bound to primate-specific LTR7/HERV-H in human embryonic stem cells [196], revealing a novel crosstalk between m6A methylation of HERV-H RNAs and DNA methylation of their loci. Specifically, they found that the HERV-H m6A modification binds m6A reader YTHDC2, which subsequently recruits the DNA 5mC demethylase TET1 to maintain expression of LTR7 loci.…”
Section: Profiling Te-associated Chromatin and Epigenetic Marksmentioning
confidence: 99%
“…Comparing the E006AA-hT and LNCaP prostate cancer cell lines, which have low versus high LINE-1 expression, respectively, they identified known LINE-1 associated TFs such as CTCF and YY1, as well as a novel LINE-1 repressor, dual phosphatase 1 (DUSP1). Sun et al used another variant of proximity labeling called "TurboID" [195] to identify factors bound to primate-specific LTR7/HERV-H in human embryonic stem cells [196], revealing a novel crosstalk between m6A methylation of HERV-H RNAs and DNA methylation of their loci. Specifically, they found that the HERV-H m6A modification binds m6A reader YTHDC2, which subsequently recruits the DNA 5mC demethylase TET1 to maintain expression of LTR7 loci.…”
Section: Profiling Te-associated Chromatin and Epigenetic Marksmentioning
confidence: 99%